Reconciling the taxation of partnerships in South Africa relative to its legal recognition. Does South African income tax legislation adequately deal with the taxation of ordinary commercial partnerships? - Haupt, Karl Alexander (Department of Finance and Tax, 2020)
i.i Research question The purpose of this dissertation is to examine whether South Africa’s approach to the taxation of ordinary partnerships flows clearly from its legal recognition thereof, or whether further clarity is needed from South Africa’s fiscal legislation i.ii Background and research method Peculiarities inherent in South Africa’s taxation of ordinary partnerships versus the legal nature of a partnership, is discussed in detail with reference to a comparison of the local treatment of foreign legal and tax systems. The legal systems of the United Kingdom, Ireland and the United States of America, have evolved out of the same common law as is recognised in South Africa, and so have already dealt with the issues illustrated in this dissertation, namely: Legally, partners own the assets of the partnership in joint and undivided shares. For tax purposes, however, each partner is treated as having a fractional interest in the assets of the partnership. The two approaches are different and give rise to an analysis as to how our tax legislation achieves conformity. Legally, when a partner 'joins’ or leaves a partnership, there is a legal dissolution of the partnership, and thereby a disposal by each partner of his or her share in the underlying assets. In tax, a disposal is likely to give rise to income and/or capital gain considerations. In the event that a legal dissolution of a partnership arises, and should the taxation consequences follow, the extent of any concomitant disposal must be determined, and whether any relief (roll-over or recognition of a divided interest) should be provided to such disposals and the subsequent consequences (such as valuation).